Total Harmonic Distortion and Power Factor Analysis of Thyristor Firing Angle on Electrostatic Precipitator in PLTU Unit 3 & 4 Pangkalan Susu Capacity 2 X 200 MW - Widjonarko, Widjonarko; Bachri, Samsul; Oktavianus, Trio Putra (Frontier Energy System and Power Engineering, 2021)
Â The impact of pollution resulting from exhaust gas in the form of coal ash in the Steam Power Plant makes the Electrostatic Precipitator an equipment that can handle these problems. The equipment has a voltage level regulation system using a thyristor which with a certain value can create an electric field capable of capturing charged ash. The thyristor system has a disturbance known as harmonics. Good handling to overcome harmonics is to measure using a certain index, one of which is the Total Harmonic Distortion (THD) and to know its effect on the power factor. In this research, an analysis of the electrostatic precipitator system at PLTU Pangkalan Susu will be carried out by collecting the necessary data and the firing angle installed in the company. From the test results, it can be said that the THD value in the Electrostatic Precipitator system at PLTU Units 3 & 4 Pangkalan Susu is in the normal range. To find out the range of compatible firing angles on the system, it is also necessary to provide a test variable angle. Based on the test, it is known that the firing angle installed in the company is 460with THDv and THDi of 4.01% and 3.61% Â respectively and the Power Factor is 0.84876. Whereas with the test variable angle, it is known that the good or normal THDv and THDi values are in the range 300to 600where the THDv value is in the range of 3.83% to 4.91% and the THDi value is in the range of 3.50% to 4. 21%.